Emerging technical risks from the application of building information modelling. Issue 3 (25th June 2020) - Aljarman, Moshabab; Boussabaine, Halim; Almarri, Khalid
Abstract : Purpose: Building information modelling (BIM) is not without risk, as the greater reliance on information technology has associated technical risks. Thus, the purpose of this paper is to assess the perceptions of the users of BIM regarding the likelihood of emergence of technical risks which might influence the successful application of BIM, to facilitate the successful implementation of BIM in the construction industry. Design/methodology/approach: The primary data were collected via a questionnaire to document the BIM risks, where 105 responses were recorded from constructors, consultants, cost consultants and other professionals from the UK construction industry. Subsequently, the analysis of the results was driven by univariate and inferential statistics (ANOVA) to assess the perception of risk emergence. Findings: The study found the most likely technical risks that might emerge from BIM application. These risks are complexity of transferring modelling data from one program to another, lack of understanding of the BIM for the different software platforms, interoperability shortcomings, failure to discover errors in the model and risks of different software platforms. Practical implications: The results will certainly intensify the discussion about BIM risks, risk allocation and all other aspects that are related to BIM contractual processes. Also, the compiled list of risks will help stakeholders in assessing financial implications that may result from BIM application. Originality/value: Important technical risks have been identified in the application of BIM. This renders a new understanding of the risks that might influence the successful application of BIM. The respondents generally agreed on the importance of the following risks: "complexity of transferring modelling data between programs from one program to another", "lack of understanding of the BIM for the different software platforms", "interoperability shortcomings", "failure to discover errors in the model" and "risks of different software platforms", which are in line with current literature.